MARKET DEVELOPMENT STRATEGY MODEL AND EFFICIENCY OF COST OF BROILER CHICKEN EGG FARMER BUSINESS IN JAMBI CITY - Raja Sarah Fatricia; Dessy Elliyana (Management Department, Faculty of Economics and Business, Universitas Jambi, 2018)
Animal Husbandry is a sub-sector that is a very important role in maintaining food security, because food from animal origin is a source of animal protein, as a basic need in meeting community nutrition. Broiler eggs are one of the commodities that have been favored by many people, but the selling price of eggs is currently increasing. The increase in egg prices is due to the smaller amount of egg supply and production in Jambi City. In general, the final goal of this study was to formulate a development strategy model and cost efficiency of broiler breeder business in Jambi City. Specifically, the objective is to formulate a market development strategy and cost efficiency of broiler breeders in Jambi City.